Predictors for Survival in an International Cohort of Patients Undergoing Distal Pancreatectomy for Pancreatic Ductal Adenocarcinoma - Korrel, M. (Ann Surg Oncol, 2020)
BACKGROUND: Surgical factors, including resection of Gerota’s fascia, R0-resection, and lymph node yield, may be associated with survival after distal pancreatectomy (DP) for pancreatic ductal adenocarcinoma (PDAC), but evidence from large multicenter studies is lacking. This study aimed to identify predictors for overall survival after DP for PDAC, especially those related to surgical technique. PATIENTS AND METHODS: Data from an international retrospective cohort including patients from 11 European countries and the USA who underwent DP for PDAC (2007–2015) were analyzed. Cox proportional hazard analyses were performed and included Gerota’s fascia resection, R0 resection, lymph node ratio, extended resection, and a minimally invasive approach. RESULTS: Overall, 1200 patients from 34 centers with median follow-up of 15 months [interquartile range (IQR) 5–31 months] and median survival period of 30 months [95% confidence interval (CI), 27–33 months] were included. Gerota’s fascia resection [hazard ratio (HR) 0.74; p = 0.019], R0 resection (HR 0.70; p = 0.006), and decreased lymph node ratio (HR 0.28; p < 0.001) were associated with improved overall survival, whereas extended resection (HR 1.75; p < 0.001) was associated with worse overall survival. A minimally invasive approach did not improve survival as compared with an open approach (HR 1.14; p = 0.350). Adjuvant chemotherapy (HR 0.67; p = 0.003) was also associated with improved overall survival. CONCLUSIONS: This international cohort identified Gerota’s fascia resection, R0 resection, and decreased lymph node ratio as factors associated with improved overall survival during DP for PDAC. Surgeons should strive for R0 resection and adequate lymphadenectomy and could also consider Gerota’s fascia resection in their routine surgical approach. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1245/s10434-020-08658-5) contains supplementary material, which is available to authorized users.